Relations between parenting styles and adolescents' moral judgment - Kadooka, Aline [UNESP]; Lepre, Rita Melissa [UNESP]; Alves Evangelista, Vitor De Morais [UNESP] (Editora Univ Leopoldlanum, 2020)
This article aims to analyze the relationship between parenting styles and adolescents' moral judgment development levels. 55 young people aged between 11 and 17 and enrolled in a Social Program from the city of Assis, in the Brazilian state of Sao Paulo, participated in this research. The instruments used were Respondingness and Demandingness Scale and the Defining Issues Test (DIT-2). The results obtained in this study indicate that the participants mainly showed a level of pre-conventional and conventional moral reasoning. In relation to parenting styles we would say that the authoritative and neglectful parents were the most prevalent. Finally, we found a relationship between of Personal Interest Schema and maternal requirement. The results suggest the need for further research on the topic.
Keywords: Parenting styles; Moral development; Adolescents